PESAN PAUS FRANSISKUS MENYIKAPI KEHADIRAN ARTIFICIAL INTELLEGENCE - Fader, Finsen; Janwarin, Iyano; Lutam, Richardo (Department of Theology - Sekolah Tinggi Filsafat Seminari Pineleng, 2024)
The essay dealt with a massage of Pope Francis concerning the developments of artificial intellegence. The presence of artificial intelligence brings a change in human life. Artificial intelligence, which was the invention of mankind in the ages of 4.0 to 5.0, is now dominating every aspect of life. Those incentive offers are provided by this artificial intelligence. However, Pope Francis, together with the Church, encouraged mankind to use it wisely. These machines are expected to help humans in their work. At the same time as the 58th World Day of Peace, Pope Francis wrote a letter to mankind. In his letter, the Pope expects artificial intelligence to contribute to world peace. So was his letter on the 57th day of social communication. He expects the use and exploitation of communication in the age of artificial intelligence to bring users to the wisdom of heart.